Regulation of the Implementation of Community Activity Restrictions in Combating Covid 19 in Bali - Kadek Julia Mahadewi (International Journal of Research in Education, 2023)
The purpose of this study is to apply the regulation of Community Activities in Bali Provision in the National Legal Order.The spread of Covid 19 has become an international and national threat.  The problem in this journal is How Effective the Regulation of Restrictions on Community Activities in Bali? and secondly the impact of the regulation of restrictions on community activities?. This writing method uses empirical research types, types of legal regulation approaches, case approaches, and approaches and uses primary and secondary data sources.  The increasing number of Covid 19 has made the Government make new regulations in its application to be able to suppress the rate of development.